Tandem Michael addition–Claisen-type condensation of anions of O-ethyl carbonates of cyanohydrins to cyclohex-2-en-1-one. Issue 13 (3rd July 2017) - Torres Domínguez, Héctor M.; Maldonado, Luis A.; Le Lagadec, Ronan
ABSTRACT: A one pot method for the synthesis of ethyl 2-acetoxy-6-aroylcyclohex-1-ene-1-carboxylates and ethyl 2-acetoxy-6-heterocarbonylcyclohex-1-ene-1-carboxylates through Michael addition of the anions of ethyl carbonates of cyanohydrins to cyclohex-2-en-1-one and subsequent reaction with acetic anhydride is described. These compounds are potential intermediates for the synthesis of 9, 10-anthraquinone and heterofused 1, 4-naphthoquinone derivatives. GRAPHICAL ABSTRACT: